Developing new tools for the study of virus - vector interactions: Sindbis virus determinants of productive midgut infection in Aedes aegypti mosquitoes - Myles, Kevin McDonald, II, author; Olson, Kenneth, advisor; Blair, Carol D., advisor (Colorado State University. Libraries, 2003)
Infectious cDNA molecular clones of SIN viruses and expression systems derived from them are powerful tools for in vivo studies of virus-vector relationships. Most SIN molecular clones have been developed from the prototype AR339 strain or closely related strains. However, AR339 viruses poorly infect Aedes aegypti mosquito midgut epithelial cells following infection by the natural oral route. A Malaysian SIN virus, MRE16, efficiently infects and disseminates from the midgut of Ae. aegypti mosquitoes after oral challenge. The observed phenotypic differences in the midgut infection and dissemination potential between the MRE16 SIN and AR339 SIN viruses represent a unique opportunity to investigate viral determinants of vector infectivity and transmissibility. These viruses were developed as a model system for the study arboviral-vector interactions in Ae. aegypti mosquitoes. The midgut infectivity, dissemination, and transmission potential of MRE16 virus and an AR339-derived virus (TR339) were compared in Ae. aegypti mosquitoes in order to further characterize observed phenotypic differences. This study determined that the significantly lower dissemination and transmission potential of TR339 virus resulted from the expression of a classic midgut escape (ME) barrier in this vector species. To further facilitate studies at the molecular level, the genome of MRE16 virus was sequenced and a full-length MRE16 cDNA infectious clone, designated MRE16ic, was constructed. MRE16ic was identical to the parental virus with regard to its ability to infect and disseminate from the midgut of Ae. aegypti mosquitoes. The power of the infectious clone technology was then demonstrated by identifying amino acid residues (E-200 to C-220), in the MRE16 virus E2 envelope glycoprotein, that were an important molecular determinant of midgut infection in Ae. aegypti mosquitoes. From knowledge of MRE16 virus determinants of vector infectivity a double subgenomic SIN (dsSIN) expression system (MRE/3'2J) was constructed in which the structural genes were derived from the MRE16 virus while the remaining genome was derived from laboratory-adapted strains of AR339 SIN virus. The midgut infectivity of MRE/3'2J in Ae. aegypti mosquitoes was similar to that of MRE16 virus. In total, this work provides a basis for additional studies that could lead to better understanding the molecular mechanisms of midgut infection and transmission barriers.
Keywords: microbiology; molecular biology; genetics; pathology